MANAGEMENT OF TRAFFIC FLOW ON A CONVEYOR TRANSPORT - Tkachev, V. V.; Protsenko, S. M. (Science and Transport Progress, 2008)
The analysis of control capability of the freight traffic volumes in coal mines, which use storage bunkers for averaging a flow from the mining sections, is carried out on the basis of imitation model of conveyor network with the use of predistribution of conveyor space, on the base of equipment SAUKL for the purpose of stabilizing the freight traffic volume and avoiding the losses during transportation.